Penerapan Sistem Pendukung Keputusan Dalam Menentukan e-Commerce Terbaik Dengan Menggunakan Metode SAW - Jenni Veronika Br Ginting (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
e-Commerce is the sale and purchase of goods or a product online for example like a consumer comes to a store that sells everything we need in everyday life and we can get it with just one finger in an application or on an official website with a network Internet. but behind the convenience there are still things that make a consumer not want to do a transaction buying and selling online because there are still many e-commerce sites that make consumers disappointed in making online transactions from the form of products received are not as good as those marketed on these online buying and selling sites, late in agreement for estimating the day of receipt of goods from the applicable provisions, and the seller's response to the buyer is bad, therefore it is necessary to implement a computer to support the decision in determining the best e-commerce, so consumers can choose which e-commerce site to visit, the method Simple Additive Weighting (SAW) is an easy method in the ranking search stage in determining a decision based on the system.